Biomechanical analysis of upper body movements between table tennis players with and without physical impairment - Yam, Jia Wen (2018)
Background: The dynamical systems theory was widely used to study human movement coordination. Purpose: This study compared the upper body movement coordination between table tennis players with physical impairment (Para) and without (Non-Para). It was hypothesized that the coordination patterns between Para and Non-Para in forehand (Forehand) and backhand topspin drive (Backhand) were different. Methods: 21 male players (10 Para, 11 Non-Para) executed 30 Forehand and 30 Backhand at an interval of 10 trials per set using a ball projection machine. Kinematics data were recorded using 3DSuit to calculate continuous relative phase angle of Forehand and Backhand Shoulder-Elbow and Elbow-Wrist couplings. Four Forehand and four Backhand were selected for each participant in the analysis Results: There was no significant difference in all couplings but differences existed in the coupling patterns. For example, Forehand Shoulder-Elbow for Para changed from positive to negative and back to positive while it was relatively neutral for Non-Para. Similarly, Backhand Elbow-Wrist for Para changed from positive to negative and back to positive in contrast with Non-Para that changed from negative to positive and back to negative. Conclusion: Although there was no coordination pattern difference between Para and Non-Para, the differences in coupling patterns suggested that successful execution was achieved through a variety of movement strategies where outcome consistency did not required movement consistency. Results from this study could be used by Team Singapore’s Para to develop effective training system and regimes.